DIAGNOSIS AND MONITORING OF TUBERCULOSIS – DIFFERENCES BETWEEN THE GENERAL POPULATION AND THOSE WITH VULNERABILITIES - Freitas, Giselle Lima de; França, Giovanna Eliza Moreira; Souza, Thaís Rodrigues de; Macário, Vanessa de Moura; Camargo, Aline Figueiredo; Protti-Zanatta, Simone; Arcêncio, Ricardo Alexandre (Cogitare Enfermagem, 2022)
Objective: to compare the performance of diagnostic exams and monitoring of tuberculosis between the general population and those in situations of social vulnerability from the municipality of Belo Horizonte/MG. Method: an epidemiological study of the tuberculosis cases recorded between 2001 and 2017 in the Information System of Belo Horizonte - Brazil. A descriptive analysis and a comparison were performed between the general population and those in street situations and deprived of their freedom. Results: diagnostic and follow-up tests were performed more frequently in vulnerable populations, in up to 30%, with low use of the rapid molecular test (mean of 35.4%) and of the observed treatment, with 22% of performance in the street population. and 38% in individuals deprived of freedom. Conclusion: the study points to the need to prioritize the rapid test and the observed treatment, especially among vulnerable groups. Disseminating the use of these tools can determine interruption of the transmission chain, the possibility of a cure and non-occurrence resistance.